HUBUNGAN ANTARA PENGETAHUAN, DUKUNGAN KELUARGA DAN PERSEPSI DENGAN PENERIMAAN VAKSIN COVID-19 DI DESA MANTOBUA KECAMATAN LOHIA KABUPATEN MUNA TAHUN 2021 - La Ode Liaumin Azim; Hariati Lestari; Iin Iin (Endemis Journal, 2022)
Reception of COVID-19 vaccination in each district/city in Southeast Sulawesi Province received different coverage. When compared to other regencies/cities, Muna Regency received very low vaccination coverage, namely 23.39% (stage 1) and 12.66% (stage 2). While in Mantobua Village the percentage of COVID-19 vaccine coverage as of October 14, 2021 is 6% (stage 1) and 2% (stage 2). This could be due to influencing factors such as the knowledge of the community itself. This study aims to determine the relationship between knowledge, family support and perception with the acceptance of the COVID-19 vaccine in Mantobua Village, Lohia District, Muna Regency in 2021. The research design used was observational analytic with a cross sectional study design. The population in this study is people who have not received the COVID-19 Vaccine, aged 12-60 years who live in Mantobua Village with a total population of 2,262 people, the number of samples in this study is 110 respondents. The sampling technique used is simple random sampling. The analysis was carried out univariate and bivariate using the chi square test. With a 95% confidence level, the research results show that there is a relationship between knowledge (p-value = 0.000), family support (p-value = 0001), perception (p-value = 0.003) and acceptance of the COVID-19 vaccine